PELAKSANAN PENERAPAN HUKUM TERHADAP PELANGGARAN MEDIA MASSA LEMBAGA PENYIARAN DI INDONESIA OLEH KOMISI PENYIARAN INDONESIA MENURUT UNDANG-UNDANG NOMOR 32 TAHUN 2002 TENTANG PENYIARAN - Kristopo; Bachtiar, Alfan; Supriyanto, Bambang Heri (E-Journal Widya Yustisia, 2020)
This article discusses the implementation of the law on violations of mass media of broadcasting commision according to law number 32 of 2002 concerning broadcasting, while the auther chose this title because until now the performance broadcasting institutions still broadcasts that are contrary to the broadcasting law such as violence, pornography, sara, which still color some broadcast-broadcasts in indonesian. The subject matter this article discusses how the role of the indonesian broadcasting commision in the mass media of broadcastinginstitutions in indonesian is continued by the factors that become obstacles in imposing punituve sanctions on mass media of broadcasting institutions then how is the process of imposing sanctions on broadcasting violations in indonesiaan. The conclusion from the discussion is that the indonesian supervisory comission plays a role in implementing the law as well as providing protection related to good broadcasting for the public. Prohibition in carrying out broadcast broadcasting activities, namely carrying out broadcasts that demean and ofend religious teachings, ideologies, individuals, group and are contrary to public morality and religious values. The methodology used in this research is normative research which uss descriptive research with a normative juridicial approach based on the prevailing laws and regulations.Broadcasting is asloprohibited from promoting liquor or other addictive substances including cigarettes. The process of resolving violations in broadcastbroadcasting must be resolved through the indonesian broadcasting commission by imposing sanctions on violations of broadcasting rules and codes of conduct and broadcasting program standars.